Death and Life in the Hands of the Translators - Tamara Cohn Eskenazi (Religions)
Taking its cue from Proverbs 18:21, which places death and life in the hands or authority of the tongue, i.e., language, this paper explores how translators throughout the millennia recomposed, through their translation choices, the story of the first couple in the garden, introducing some deadly consequences with their choices.